Association of PELI1 polymorphisms in systemic lupus erythematosus susceptibility in a Chinese population. (September 2015) - Chen, F-R; Zhai, Z-F; Shi, X-W; Feng, L; Zhong, B-Y; Yan, W-J; Wang, H; Chen, Y; You, Y; Luo, N; Zhang, D-M; Hao, F
Objective: Studies in animal models have indicated that Pellino 1 is involved in inflammatory and autoimmune diseases, such as systemic lupus erythematosus (SLE). The current study was designed to determine whether PELI1 confers genetic susceptibility to SLE in humans, as assessed in a Chinese Han population. Methods: Blood samples were drawn from patients diagnosed with SLE and healthy volunteers. Three single nucleotide polymorphism (SNP) loci with a minor allele frequency of at least 0.05 were chosen to evaluate the correlation between PELI1 genotype and the incidence of SLE. Results: There was a significant difference in the frequency distribution of the rs329497 allele between the SLE patients and the healthy controls (A vs. G; Bonferroni corrected p  = 0.036, odds ratio = 0.75, 95% confidence interval = 0.60–0.94). No differences in the genotype and allele frequencies of other SNP loci were observed between the two groups. Furthermore, the alleles and genotypes of the three SNPs were not associated with lupus nephritis. Conclusion: In the Chinese Han population, PELI1 SNPs may be associated with SLE susceptibility.